How Scientists and Prophets have to Collaborate to Face a NEO Threat - Arnould, Jacques (European Journal of Applied Sciences, 2025)
In the case of any scientifically proved NEO threat, space agencies, scientific institutions and governments worldwide would have to face the most complicated of all challenges: finding a way to convince populations of the reality of the danger, to be able to find ways to prevent it. The slowness, or the absence of reactions towards the threats generated by global warming, biosphere pollution, depletion of the biodiversity, and extensive use of nuclear energy for energetic or military purposes, cast doubt on the capacity of reaction and mobilisation of civil societies faced with major catastrophes, even the most obvious. In his book “The Imperative of Responsibility”, Hans Jonas mentions the role of fear in the capacities of a society to face its responsibilities and act accordingly. But is fear enough in the very case of NEO? Actually, this threat dwells into our ancient and collective conscience and belief, and the vision we have over human history is particularly pessimistic. Moreover, it is not granted that the representation of the universe is yet completely free from the Aristotelian duality, which separates and opposes Earth, the lower world, and Cosmos, the upper world. Scientific information today can contribute to that representation, without people even being aware of it. Today, scientific knowledge does not seem enough to convince humans to support a voluntarist and international policy which could lead to an efficient strategy against a NEO threat response. Men are conscious of it, but not afraid. To the “knowledge” offered and shared by the scientist, we should combine the “belief” that the prophet exposes to us. The prophetic mission is not only to frighten populations by evoking, or even imagining, a catastrophic (apocalyptic) future. Its first role is to raise a lucid and reasonable consciousness of the present situation. Then and only then is it possible to foresee the future, and possibly to try and modify it, without falling into fatalism. With NEO, no need, or rather no reason to imagine, or to fantasise over a future of mankind that would be driven and mastered by human desire. The objective is merely to try to preserve our species against an exterior threat, a threat that is totally beyond our control. From that moment, humans cannot refer themselves to what they wish they were, but to what they are already, in their fragility, their dissensions, their jealousy and their pursuit of power. A NEO is not just a threat to the integrity of the biosphere, but also to the understanding humans have of themselves. And it is undoubtedly for that very reason that NEO represent a danger that is difficult to handle.